Organic silicon film with loose transition layer and preparation method and application thereof

By doping carbon nanotubes and SiO2-ZrO2 sol in the silicone film to form a loose transition layer, the problem of insufficient stability of the existing film in the acidic environment is solved, and higher permeability flux and separation factors are achieved.

CN119386680AActive Publication Date: 2025-02-07CHANGZHOU UNIV

Patent Information

Application Number
CN202411507888.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing silicone films are insufficient in acidic and hydrothermal environments, and the traditional transition layer preparation process is complex and the porosity is low, resulting in a loss of permeability.

Method used

Carbon nanotubes are doped with SiO2-ZrO2 sol, and a loose transition layer is formed on the ceramic support by spin coating, and an organic silicon film is calcined at high temperature.

Benefits of technology

The water permeability flux and separation factors of the membrane are improved, the stability in acidic and hydrothermal environments is enhanced, and the number of coatings and defective problems are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386680A_ABST
    Figure CN119386680A_ABST
Patent Text Reader

Abstract

The invention discloses an organic silicon film with a loose transition layer and a preparation method and application of the organic silicon film, and belongs to the technical field of film separation. The preparation method comprises the following steps: reacting carbon nanotubes with acid, washing and drying to obtain carboxylated carbon nanotubes COOH-CNTs; uniformly mixing the COOH-CNTs with the SiO2-ZrO2 sol, so as to obtain a COOH-CNTs / SiO2-ZrO2 sol; coating a tubular ceramic support body with the porous transition layer, and calcining to obtain a ceramic support body with a loose transition layer; and coating the obtained ceramic support body with the loose transition layer with organic silicon sol, and carrying out heat treatment to form a separation layer, thereby obtaining the organic silicon film. According to the COOH-CNTs, sol particles can be dispersed into a linear grid, and the COOH-CNTs have hydrophilicity and a pore structure, so that more water molecules can quickly pass through the COOH-CNTs, the permeation resistance of the water molecules in a transition layer and a separation layer is reduced, and the COOH-CNTs shows better separation performance in a solution of a pervaporation separation solvent / water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane separation, and in particular relates to an organic silicon membrane with a loose transition layer and a preparation method and application thereof. Background Art

[0002] Pervaporation membranes for solvent / water separation are in great demand in industry. The pervaporation technology for dehydration of acidic organic matter, such as acetic acid dehydration or dehydration of organic solvents in acidic environment, has very high requirements on the acid resistance of the membrane.

[0003] The stability of organosilicon membranes in acidic and hydrothermal environments is better than that of polymer membranes and inorganic membranes. Organosilicon membranes are generally multi-layer asymmetric structures composed of a support and a separation layer. The support mainly provides sufficient mechanical strength, while the separation layer mainly plays a screening role. The pore size of the ceramic support is large and the surface is rough, so a transition layer needs to be introduced to reduce the pore size and surface roughness. However, the traditional transition layer preparation process is complicated. Usually, materials with similar structures such as silica sol and alumina sol particles are loaded on the support. Through multiple coatings, the pores accumulated between the particles are reduced in pore size. This method results in a low porosity of the transition layer, a long mass transfer path, and loss of membrane permeation flux during pervaporation.

[0004] At present, the preparation of organosilicon membranes usually adopts the rubbing method or the dip coating method (Waseem Raza, et al. HCl modification and pervaporation performance of BTESE membrane for the dehydration of acetic acid / water mixture [J]. Separation and Purification Technology, 2020, 235: 116102; Hessel L. Castricum, et al. High-performance hybrid pervaporation membranes with superior hydrothermal and acid stability [J]. Journal of Membrane Science, 2008, 324: 111-118). The rubbing method usually leads to low repeatability of membrane preparation and is prone to incomplete coating defects. The membrane layer formed by the dip coating method is thicker and prone to cracking, and exhibits a lower separation factor in pervaporation. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide an organic silicon film with a loose transition layer and a preparation method and application thereof in view of the deficiencies in the prior art.

[0006] Technical solution: The purpose of the present invention is achieved through the following technical solution:

[0007] The present invention provides a method for preparing an organic silicon film having a loose transition layer, comprising the following steps:

[0008] (1) reacting carbon nanotubes with acid, washing, and drying to obtain carboxylated carbon nanotubes COOH-CNTs;

[0009] (2) adding water to the COOH-CNTs and SiO2-ZrO2 sol obtained in step (1), mixing them evenly, and obtaining a COOH-CNTs / SiO2-ZrO2 sol;

[0010] (3) coating the COOH-CNTs / SiO2-ZrO2 sol prepared in step (2) onto a tubular ceramic support, and calcining to obtain a ceramic support having a loose transition layer;

[0011] (4) coating the organic silicon sol onto the ceramic support having the loose transition layer obtained in step (3), and subjecting the ceramic support to heat treatment to form a separation layer, thereby obtaining the organic silicon film.

[0012] The COOH-CNTs of the present invention enable the sol particles to be dispersed in a linear grid, and have hydrophilicity and a pore structure, which can allow more water molecules to pass quickly, reducing the permeation resistance of water molecules in the transition layer and the separation layer, and showing good separation performance in the pervaporation separation solvent / water solution.

[0013] Preferably, in step (1), the acid is a mixture of concentrated sulfuric acid and concentrated nitric acid, and the volume ratio of the two is 3:1; the reaction temperature is 60-100° C., and the reaction time is 2-4 h.

[0014] Preferably, in step (1), the washing method is to wash with deionized water and ethanol alternately until neutral.

[0015] Preferably, in step (1), the drying temperature is 50-80° C., and the drying time is 12-24 hours.

[0016] A further preferred embodiment of the present invention is that in step (1), the preparation method of COOH-CNTs is to place carbon nanotubes in sulfuric acid (98%) and nitric acid (68%) at 100°C for a reaction time of 4 hours, and then wash them alternately with deionized water and ethanol until neutral, and then dry them to obtain COOH-CNTs.

[0017] Preferably, in step (2), the mass ratio of the COOH-CNTs to the SiO2-ZrO2 sol is 1-7%.

[0018] In the present invention, the SiO2-ZrO2 sol is prepared according to the preparation method of CN113058447A.

[0019] The four substances were mixed together in a molar ratio of 1:5:10:2 of tetraethyl orthosilicate: zirconium n-butoxide: ethanol: hydrochloric acid. The water content was adjusted so that the mass fraction of tetraethyl orthosilicate and zirconium n-butoxide was maintained at 2wt%. The solution was then heated to 100°C and kept boiling for 6 hours to form a stable SiO2-ZrO2 sol.

[0020] Preferably, in step (3), the coating method is spin coating, and the spin coating is to fix the tubular ceramic support on an iron rod and rotate it, place the COOH-CNTs / SiO2-ZrO2 sol below, load it onto the support at a low speed, and perform rotary evaporation at a high speed;

[0021] The low speed is a rotation speed of 10-100 rpm, and the high speed is a rotation speed of 600-6000 rpm, which is maintained for 30-60 seconds.

[0022] Preferably, in step (3), preheating is performed before calcination, the preheating temperature is 100-200° C., and the preheating time is 5-10 min.

[0023] Preferably, in step (3), the calcination temperature is 450-550° C., the calcination time is 20-60 min, and the coating and calcination are repeated 2-6 times.

[0024] Preferably, in step (4), the organosilicon sol is prepared by hydrolysis polymerization of an organosilicon source precursor under the catalysis of an acidic catalyst.

[0025] Furthermore, the organic silicon source precursor may be 1,2-bis(triethoxysilyl)ethane (BTESE) or bis(triethoxysilyl)methane (BTESM).

[0026] A further preferred embodiment of the present invention is that the organic silicon source precursor is 1,2-bis(triethoxysilyl)ethane (BTESE).

[0027] Furthermore, the acidic catalyst may be hydrochloric acid, sulfuric acid or nitric acid.

[0028] Furthermore, the acidic catalyst is selected from hydrochloric acid.

[0029] Preferably, in step (4), the coating method is spin coating.

[0030] A specific further preferred embodiment of the present invention is that the spin coating method is to coat the organosilicon sol onto the tubular ceramic support containing the loose transition layer at a low rotation speed of 20 rpm, and then increase the rotation speed to 1000 rpm and maintain it for 30 seconds.

[0031] Preferably, in step (4), the heat treatment is calcination in an air atmosphere at 100-250° C. for 30-60 min.

[0032] The present invention also provides an organic silicon film with a loose transition layer prepared by the above preparation method.

[0033] The present invention also provides application of the organic silicon membrane with a loose transition layer in pervaporation technology.

[0034] The above-mentioned organic silicon membrane with a loose transition layer is placed in a membrane module to perform pervaporation separation of solvent / water solution.

[0035] The present invention also provides a method for dehydrating an acidic system by pervaporation, wherein the organic silicon membrane with a loose transition layer is used for pervaporation of an acetic acid aqueous solution with a mass fraction of 90wt%, wherein the acetic acid aqueous solution is heated to 75°C and the permeation side is evacuated (<400Pa).

[0036] Beneficial effects:

[0037] The present invention prepares an organosilicon membrane with a loose transition layer by doping COOH-CNTs into SiO2-ZrO2 sol and coating the sol onto a tubular ceramic support by spin coating. By doping COOH-CNTs, the sol particles are dispersed in the nanotube network, the compactness of the silicon-zirconium network structure is reduced, the number of coatings is reduced, and the membrane is applied to the dehydration separation of pervaporation acetic acid / water solution to improve the water permeation flux and separation factor. On the one hand, COOH-CNTs disperse the dense sol particles, and the structure itself has pores, which can be used as an additional transmission channel for water molecules, and the carboxyl groups contained in the membrane further serve as hydrophilic sites to enhance the adsorption of water, all of which improve the transmission efficiency of water molecules in the membrane, and are conducive to improving the water flux in the pervaporation separation of solvent and water. On the other hand, by spin coating, the defective problems caused by rubbing and dipping are reduced, and the separation performance of the membrane is increased. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a SEM image of the organic silicon film prepared in Example 1;

[0039] Figure 2 is a SEM image of the organic silicon film prepared in Comparative Example 1;

[0040] Figure 3Schematic diagram of water molecules passing through the transition layer of the organic silicon membrane. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is described in detail below through specific embodiments, but the protection scope of the present invention is not limited to the embodiments.

[0042] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.

[0043] The SiO2-ZrO2 sol used in the examples and comparative examples of the present invention was prepared by referring to the preparation method of CN113058447A.

[0044] The four substances were mixed together in a molar ratio of 1:5:10:2 of tetraethyl orthosilicate: zirconium n-butoxide: ethanol: hydrochloric acid. The water content was adjusted so that the mass fraction of tetraethyl orthosilicate and zirconium n-butoxide was maintained at 2wt%. The solution was then heated to 100°C and kept boiling for 6 hours to form a stable SiO2-ZrO2 sol.

[0045] Example 1 Preparation of an organic silicon film with a loose transition layer

[0046] (1) Single-walled carbon nanotubes were placed in a mixture of concentrated sulfuric acid (98%) and concentrated nitric acid (68%) (V H2SO4 / V HNO3 =3 / 1), stirred and refluxed at 100°C for 4h, then washed alternately with deionized water and ethanol until neutral, and finally dried in a vacuum drying oven at 80°C for 24h to obtain carboxylated carbon nanotubes COOH-CNTs.

[0047] (2) Take 3 mg of COOH-CNTs and 5 g of 2 wt% SiO2-ZrO2 sol, add deionized water to the total system to 20 g, and after ultrasonic treatment for 1 hour, a uniformly dispersed COOH-CNTs / SiO2-ZrO2 sol is obtained. The mass ratio of COOH-CNTs to SiO2-ZrO2 sol in the obtained sol is 3 wt%.

[0048] (3) Fix the tubular ceramic support on an iron rod and rotate it, place the COOH-CNTs / SiO2-ZrO2 sol underneath, load the sol onto the support at a low speed of 20 rpm, and then remove the sol; increase the speed to 1000 rpm and maintain it for 60 seconds for rotary evaporation. Preheat the tubular ceramic support in an oven at 200°C for 5 minutes, then heat it in a tubular furnace at 550°C for 20 minutes, repeat 6 times, and obtain a ceramic support with a loose transition layer.

[0049] (4) 1 g of 1,2-bis(triethoxysilyl)ethane (BTESE) was added to 10 g of ethanol, and then 10 g of water and 0.05 g of hydrochloric acid were added for catalysis, and the mixture was stirred at room temperature for 2 h to obtain an organic silica sol. The separation layer was prepared by spin coating, and the organic silica sol was coated on a tubular ceramic support containing a loose transition layer at a low speed of 20 rpm, and the speed was increased to 1000 rpm and maintained for 30 s. After coating, the mixture was calcined in air at 250° C. for 30 min to obtain an organic silica film. Figure 1 This is a SEM image of the prepared organic silicon film. It can be seen from the image that the surface of the prepared film is continuous without obvious defects.

[0050] The organosilicon membrane was used for the pervaporation test of 90 wt% acetic acid aqueous solution, where the acetic acid aqueous solution was heated to 75°C and the permeate side was evacuated (<400 Pa). The separation performance was: the flux was 2.13 kg·m -2 ·h -1 , the separation factor is 1312.

[0051] Example 2

[0052] The process of preparing the organic silicon film is basically the same as that in Example 1, the difference is that in the COOH-CNTs / SiO2-ZrO2 sol, the amount of SiO2-ZrO2 sol is kept unchanged, and the mass ratio of COOH-CNTs to SiO2-ZrO2 sol is 1wt%.

[0053] The organosilicon membrane was used for the pervaporation test of 90 wt% acetic acid aqueous solution, where the acetic acid aqueous solution was heated to 75°C and the permeate side was evacuated (<400 Pa). The separation performance was: the flux was 1.94 kg·m -2 ·h -1 , the separation factor is 1033.

[0054] Example 3

[0055] The process of preparing the organic silicon film is basically the same as that in Example 1, the difference is that in the COOH-CNTs / SiO2-ZrO2 sol, the amount of SiO2-ZrO2 sol is kept unchanged, and the mass ratio of COOH-CNTs to SiO2-ZrO2 sol is 5wt%.

[0056] The organic silicon membrane was used for the pervaporation test of 90 wt% acetic acid aqueous solution, where the acetic acid aqueous solution was heated to 75°C and the permeate side was evacuated (<400 Pa). The separation performance was: the flux was 2.33 kg·m -2 ·h -1 , the separation factor is 596.

[0057] Example 4

[0058] The process of preparing the organic silicon film is basically the same as that in Example 1, the difference is that in the COOH-CNTs / SiO2-ZrO2 sol, the amount of SiO2-ZrO2 sol is kept unchanged, and the mass ratio of COOH-CNTs to SiO2-ZrO2 sol is 7wt%.

[0059] The organic silicon membrane was used for the pervaporation test of 90 wt% acetic acid aqueous solution, where the acetic acid aqueous solution was heated to 75°C and the permeate side was evacuated (<400 Pa). The separation performance was: the flux was 2.45 kg·m -2 ·h -1 , the separation factor is 312.

[0060] It can be seen from Examples 1-4 that as the doping amount increases, the membrane flux increases accordingly, and the separation factor first increases and then decreases. The reason for the decrease is that when the doping amount reaches a certain level, COOH-CNTs will agglomerate, resulting in increased interface defects in the transition layer and a decrease in the separation factor.

[0061] Comparative Example 1

[0062] The tubular ceramic support was fixed on an iron rod, and SiO2-ZrO2 sol was placed underneath. The sol was loaded onto the support at a low speed of 20 rpm, and then the speed was increased to 1000 rpm and maintained for 60 seconds for rotary evaporation. Finally, the tubular ceramic support was preheated in an oven at 200°C for 5 minutes, and then placed in a tubular furnace at 550°C for 20 minutes, and repeated 6 times.

[0063] The BTESE separation layer was prepared by spin coating. The organosilicon sol prepared in Example 1 was coated on a tubular ceramic support containing a transition layer at a low rotation speed of 20 rpm, and the rotation speed was increased to 1000 rpm and maintained for 30 seconds. After coating, it was calcined in air at 250°C for 30 minutes to obtain an organosilicon film. Figure 2 This is a SEM image of the prepared organic silicon film. It can be seen from the image that the surface of the prepared BTESE film is smooth and continuous.

[0064] The organosilicon membrane was used for the pervaporation test of 90 wt% acetic acid aqueous solution, where the acetic acid aqueous solution was heated to 75°C and the permeate side was evacuated (<400 Pa). The separation performance was: the flux was 1.31 kg·m -2 ·h -1 , the separation factor is 1429.

[0065] Comparative Example 2

[0066] The transition layer was prepared by rubbing coating. SiO2-ZrO2 sol was rubbed on the tubular ceramic support, and then calcined at 550°C for 20 minutes. This was repeated 6 times to complete the coating of the transition layer.

[0067] The separation layer was prepared by rubbing coating. The organic silicon sol prepared in Example 1 was rubbed onto a tubular ceramic support containing a transition layer, and then calcined at 250° C. for 30 min to obtain an organic silicon film.

[0068] The organic silicon membrane was used for the pervaporation test of 90 wt% acetic acid aqueous solution, where the acetic acid aqueous solution was heated to 75 °C and the permeate side was evacuated (<400 Pa). The separation performance was: the flux was 1.53 kg·m -2 ·h -1 , the separation factor is 977.

[0069] Comparative Example 3

[0070] The transition layer was prepared by rubbing method. SiO2-ZrO2 sol was rubbed onto the tubular ceramic support, calcined at 550°C for 20 minutes, and repeated 10 times to complete the coating of the transition layer.

[0071] The separation layer was prepared by rubbing coating. The organic silicon sol prepared in Example 1 was rubbed onto a tubular ceramic support containing a transition layer, and then calcined at 250° C. for 30 min to obtain an organic silicon film.

[0072] The organic silicon membrane was used for the pervaporation test of 90 wt% acetic acid aqueous solution, where the acetic acid aqueous solution was heated to 75°C and the permeate side was evacuated (<400 Pa). The separation performance was: the flux was 1.23 kg·m -2 ·h -1 , the separation factor is 1450.

[0073] Comparing Comparative Example 1 with Examples 1-4, it can be seen that the organic silicon membrane doped with the COOH-CNTs transition layer has a higher flux. Figure 3 Schematic diagram of water molecules passing through the transition layer of the organic silicon film. It can be seen from the figure that in the transition layer without COOH-CNTs, water molecules can only pass through the gaps between the SiO2-ZrO2 sols, while in the transition layer doped with COOH-CNTs, water molecules can also be quickly transported through the channels in the COOH-CNTs. Comparative Examples 2-3 Compared with Comparative Example 1, it can be seen that the performance of the film prepared by the spin coating method is equivalent to that of the film prepared by the wipe coating method, but the number of coatings by the spin coating method is less.

[0074] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention as defined in the appended claims.

Claims

1. A method for preparing an organic silicon film having a loose transition layer, characterized in that: The following steps are involved: (1) reacting carbon nanotubes with acid, washing, and drying to obtain carboxylated carbon nanotubes COOH-CNTs; (2) adding water to the COOH-CNTs and SiO2-ZrO2 sol obtained in step (1), mixing them evenly, and obtaining a COOH-CNTs / SiO2-ZrO2 sol; (3) coating the COOH-CNTs / SiO2-ZrO2 sol prepared in step (2) onto a tubular ceramic support, and calcining to obtain a ceramic support having a loose transition layer; (4) coating the organic silicon sol onto the ceramic support having the loose transition layer obtained in step (3), and subjecting the ceramic support to heat treatment to form a separation layer, thereby obtaining the organic silicon film.

2. The preparation method according to claim 1, characterized in that: In step (1), the acid is a mixture of concentrated sulfuric acid and concentrated nitric acid, and the volume ratio of the two is 3:1; the reaction temperature is 60-100° C., and the reaction time is 2-4 hours.

3. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the COOH-CNTs to the SiO2-ZrO2 sol is 1-7%.

4. The preparation method according to claim 1, characterized in that: In step (3), the coating method is spin coating, and the spin coating is to fix the tubular ceramic support on an iron rod and rotate it, place the COOH-CNTs / SiO2-ZrO2 sol underneath, load it onto the support at a low speed, and perform rotary evaporation at a high speed; the low speed is a rotation speed of 10-100 rpm, and the high speed is a rotation speed of 600-6000 rpm, maintained for 30-60s.

5. The preparation method according to claim 1, characterized in that: In step (3), preheating is performed before calcination, the preheating temperature is 100-200° C., and the preheating time is 5-10 minutes.

6. The preparation method according to claim 1, characterized in that: In step (3), the calcination temperature is 450-550° C., the calcination time is 20-60 min, and the coating and calcination are repeated 2-6 times.

7. The preparation method according to claim 1, characterized in that: In step (4), the organosilicon sol is prepared by hydrolysis polymerization of an organosilicon source precursor under the catalysis of an acidic catalyst.

8. The preparation method according to claim 1, characterized in that: In step (4), the heat treatment is calcination in an air atmosphere at 100-250° C. for 30-60 min.

9. The organic silicon film having a loose transition layer prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the organic silicon membrane with a loose transition layer according to claim 9 in pervaporation technology, characterized in that: The organic silicon membrane with a loose transition layer as claimed in claim 9 is placed in a membrane assembly to perform pervaporation separation of solvent / water solution.

Citation Information

Patent Citations

  • Asymmetrically-structural ceramic ultrafiltration membrane and preparation method thereof

    CN101791524A

  • Carbon nano tube-polymer composite nanofiltration membrane and preparation method thereof

    CN101890315A

  • Preparation method of organosilicon film and application of organosilicon film in pervaporation treatment of high-salinity wastewater

    CN106110909A

  • Solvent-resistant bridged polysilsesquioxane nanofiltration composite membrane and preparation method thereof

    CN111603950A

  • Binder-coupled carbon nanostructure nano-porous membrane and manufacturing method therefor

    IN201747025215A

Cited By

  • Organosilicon membrane having loose transition layer and preparation method therefor and use thereof

    WO2026092414A1